Relationship between Anxiety Levels and Smoking Behavior in Early Adolescents in Nias Ciranjang Junior High School - Radina Ratnasari; Dewi Umu Kulsum; Dwi Hastuti (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Background: Adolescence is a period in which a child experiences a transition from childhood to adulthood both physically and psychologically. In 2018 the prevalence of smokers in the population aged >10 years in Indonesia, especially West Java, was ranked first at 32.0%, while the smoking prevalence in the population aged 10-18 years was 9.1% in 2018, this number increased from 2013 which was only 7.2%. Mental health is important in determining the quality of a nation. The phenomenon when the incidence of health problems in adolescents increases, the underlying cause comes from internal and external factors, this problem is still a threat if not treated immediately. Objective: This study aims to determine the relationship between anxiety levels and smoking behavior in early adolescents. Methods: The research design used is a correlation study with a cross sectional design. The number of samples was 55 male students in grades 7 and 8 in Nias Ciranjang junior high school which were selected through purposive sampling technique. Data collection filled out the Depression Anxiety Stress Scale 42 (DASS 42) questionnaire, rcount > rtable 0,514 and ralpha value = 0,952. Data analysis was carried out univariate (frequency distribution) and bivariate with chi square test. Result: The results showed that some respondents had moderate anxiety levels as much as 54.5%, most respondents had bad smoking behavior as much as 54.5%, and there was a relationship between anxiety levels and smoking behavior in early adolescents in Nias Ciranjang junior high school with p -value=0.001. Conclusion: It is hoped that nursing science and schools will continue to improve students' understanding of the dangers of smoking through counseling or other activities so that there are no more teenagers smoking.